A two-year follow-up study of the PCV2 status of a Danish pig herd that was initially assumed to be PCV2-free. Issue 1 (December 2015) - Kristensen, Charlotte; Hjulsager, Charlotte; Larsen, Lars
Abstract Background A longitudinal study was carried out to investigate whether a herd that had previously tested negative for porcine circovirus type 2 (PCV2) by polymerase chain reaction (PCR) was free of PCV2 or whether the negative profiles indicate that the level of PCV2 varies over time. Results In eight Danish herds that had initially tested negative for PCV2 by quantitative polymerase chain reaction (PCR), additional sampling was performed. Only one of the herds was still PCV2-negative in the additional sampling and was included in the study. The herd was a finishing herd, subclinically infected with PCV2, but vaccinated against PCV2 to improve performance. The herd was monitored by taking blood samples every seventh week over a period of two years and was not found to be continuously negative for PCV2 by PCR. The first time PCV2 was detected by PCR, in May 2010, PCV2 vaccination had been withdrawn from the herd, and at the same time the herd was infected with porcine reproductive and respiratory syndrome virus (PRRS). The PCV2-negative status, measured by PCR, was obtained in the first sampling after the PCV2 vaccination had been reintroduced. When PCV2 vaccination was withdrawn again in September 2011, the herd tested positive for PCV2 by PCR, and this time it continued to be PCV2-positive, even though PCV2 vaccination had been reintroduced. Conclusion A Danish finishing herd that appeared to be PCV2-free from the start of a period of two years was not free of PCV2 during the entire period.